Special Issue: Wireless Sensor and Actuator Networks for Smart Cities - Burak Kantarci; Sema F. Oktug (Journal of Sensor and Actuator Networks, 2018)
Our lives are being transformed by the interplay between mobile networks, wireless communications, and artificial intelligence. [...]